The anarchical society a study of order in World politics - Bull, Hedley (New York Columbia University Press, 2012)
In this fundamental text, Hedley Bull explores three key questions: What is the nature of order in world politics? How is it maintained within the contemporary states system? And do desirable and feasible alternatives to the states system exist? Contrary to common claims, Bull asserts that the sovereign states system is not in decline. Rather, it persists and thrives, as it is essential to maintaining an international world order.
Includes bibliographical references (p. 309-319) and index.
Keywords: International organization